GENDER DIFFERENCES OF CLINICAL MANIFESTATION AND CARDIAC REMODELING IN IDIOPATHIC HYPERTROPHIC CARDIOMYOPATHY IN ELDERLY PATIENTS - A. A. Poliakova; E. I. Baranova; E. N. Semernin; A. N. Krutikov; O. V. Melnik; S. A. Pyko; V. G. Davydova; A. A. Kostareva; A. Ya. Gudkova (Российский кардиологический журнал, 2018)
Aim. To study gender differences of clinical course and myocardial remodeling in elderly patients with idiopathic hypertrophic cardiomyopathy (HCM).Material and methods. The study included 131 patients with idiopathic HCM. Patients underwent standard clinical, laboratory and instrumental diagnostics.Results. In the elderly patients with idiopathic HCM, proportion of females was 63% (n=82), males — 37% (n=49). Mean age of females 69±7 y. o., males — 68±7 y. o. Coronary artery disease (CAD) was more common in males (32%) than in females (22%), but with no significant difference (p=0,2). Atrial fibrillation was more common in males (49% vs 29%, respectively, p=0,03). Size of the left atrium and enddiastolic size of the left ventricle in males exceeded those in females (51,2±9,0 mm versus 46,3±4,7 mm, 51,5±7,6 mm versus 45,6±5,7 mm, respectively, p=0,01). In males, symmetrical myocardial remodeling was found more often (42% vs 25%, p=0,04). Obstructive form of HCM was predominant in females (45% and 14%, p=0,01). Chronic heart failure (CHF) with NYHA class III was found in 29% in female group (n=24) and in 12% in male group (n=6), with a tendency to difference (p=0,06). In females, CHF with NYHA class III was mostly due to the left ventricle outflow tract obstruction (n=13) and dilatation phase (n=3). In males, almost all cases of CHF in NYHA class III-IV (8 of 9 patients) were a result of combination of HCM with CAD and previous myocardial infarction. In males, the ejection fraction was significantly lower (55,7±14,8% versus 62,2±10,9%, p=0,01).Conclusion. Proportion of females was higher in elderly patients with idiopathic HCM. Females with HCM were characterized by a more severe course of the disease due to the left ventricle outflow tract obstruction and dilatation phase. In males with idiopathic HCM there were registered more often the following: atrial fibrillation, larger left atrium and end-diastolic size of the left ventricle, symmetrical myocardial remodeling, lower ejection fraction of the left ventricle, — probably associated with a combination of HCM with CAD and previous myocardial infarction.